Penggunaan Media Sosial Instagram @Mardanialisera dalam Meningkatkan Elektabilitas di Pemilihan Legislatif Tahun 2024 - Maryam Maryam; Muh. Ruslan Ramli (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to evaluate how the management of Mardani Ali Sera’s Instagram account @Mardanialisera towards increasing positive netizen comments in the 2024 legislative elections. The method used in this research is a qualitative approach with a case study design. Data were collected through direct observation, interviews, and analysis of the types and frequencies of posted content, as well as the interactions between the account and its followers. The results show that the Instagram usage strategy has a significant impact on Mardani Ali Sera's electability. The strategy includes, first, building a consistent content flow with the 3A principles (Safe, Fun, Cool) and raising criticism that fosters public discussion. Second, utilizing Instagram features such as Reels, Live, Comment, Like, Direct Message, and Share to effectively convey political messages. Additionally, the use of ads and promotions strengthens interactions with Generation Z, the main consumers of internet technology. Third, Instagram allows Mardani Ali Sera to build a unique news pattern, following the